mHealth to enhance oral cancer awareness in older adults in Chile: a preliminary report - Constanza B. Morales-Gómez; Iris L. Espinoza-Santander; Leonardo López-Neira; Alfredo H. von Marttens; Marjorie C. Borgeat; Ximena M. Lee; Marco A. Cornejo-Ovalle; Jorge A. Gamonal; Andrea C. Paula-Lima; Rodrigo A. Giacaman; Soraya León; Víctor Beltrán (Exploration of Digital Health Technologies)
This study aims to assess a new mobile application (app)’s efficacy in raising oral cancer awareness among older adults through educational videos and serious games. The app, named TEGO® (Tele-platform of Geriatric and Dental Specialties), with a video about oral cancer prevention, oral-self-examination, and serious gaming elements, like trivia and word search puzzles to reinforce the acquired knowledge was developed. Fifty-six patients, aged 60 to 80 years, were randomly selected from the Dental Clinic of the University of Chile and invited to use the app on their personal smartphones. Knowledge and attitudes were evaluated before two and four weeks after use. Oral self-examination practices were measured with a checkup guideline. The participation rate was 41.1%, mostly male (52.2%). Before using the app, 30.4% of the participants reported awareness of oral cancer, and none had performed oral self-examinations. Following two weeks after use, there was notable engagement, with 100% of participants utilizing it and responding that they had heard about oral cancer, and 56.5% having practiced an oral self-examination. This last outcome increased to 82.6% in the fourth week. The use of mHealth technologies has the potential as an effective educational tool for disseminating knowledge about oral cancer among older adults.